PENGARUH PEMBERDAYAAN DAN BUDAYA ORGANISASI TERHADAP PROFESIONALISME DOSEN - Andardinata, Ady (Jurnal Minds: Manajemen Ide dan Inspirasi, 2017)
This study aims to analyze the influence of empowerment and organizational culture on professionalism. This research is quantitative in which the research data is analyzed descriptively using Excel 2007 program and inferentially using multiple linear regression model with the help of SPSS 23 IBM program for hypothesis testing. The hypothesis in this study are: empowerment and organizational culture have a positive and significant impact on professionalism. The result of the analysis shows that empowerment and organizational culture have positive effect to professionalism. The value of the correlation coefficient (r) of 0.506 means the closeness of the relationship between empowerment and organizational culture to professionalism in a moderate level. The value of determination coefficient ( ) of 0.256% means that empowerment and organizational culture influence 25.6% on professionalism which means there are other variables of 74.4% which can affect professionalism. The f-test shows that empowerment and organizational culture simultaneously have a significant effect on professionalism. The t-test shows that empowerment is partially significant to professionalism while the organizational culture is partially influential not significant to professionalism.